Changes in Compliance With Personal Preventive Measures and Mental Health Status Among Chinese Factory Workers During the COVID-19 Pandemic: An Observational Prospective Cohort Study - Yuan, Jinqiu; Cao, Bolin; Zhang, Changhua; Chan, Paul Shing-fong; Xin, Meiqi; Fang, Yuan; Chen, Yaoxi; Huang, Dongfeng; Li, Lifang; Xuan, Xujun; Zhang, Gengpeng; Pan, Yihang; et al. (Frontiers in Public Health, 2022)
Coronavirus Disease 2019 (COVID-19) vaccination together with good compliance with personal preventive measures may help eradicate the ongoing pandemic. This observational prospective cohort study investigated the changes in compliance with personal preventive measures, depressive symptoms and sleep quality among factory workers within a 3-month follow-up period. A total of 663 workers were recruited by a stratified two-stage cluster sampling in March 2020, and all of them completed a follow-up survey three months later. Multilevel logistic and linear regression models (level 1: factories; level 2: individual participants) were fitted. A significant decline was observed in consistent facemask wearing in workplace (from 98.0% to 90.3%, P<.001) and in other public spaces (from 97.1% to 94.4%, P=.02), sanitizing hands (from 70.9% to 48.0%, P<.001), household disinfection (from 47.7% to 37.9%, P<.001) and moderate-to-severe depression (from 6.0% to 0.6%, P<.001) over the follow-up period. A significant improvement in avoiding crowded places (from 69.8% to 77.4%, P=.002) and sleep quality (proportion of participants reporting poor sleep quality dropped from 3.9% to 1.2%, P=.002) was also observed. Efforts are needed to maintain compliance with personal preventive measures during the pandemic. Mental health problems were uncommon and likely to be one-off among Chinese factory workers.